Association of serum fibroblast growth factor 23 (FGF23) and incident fractures in older men: The Osteoporotic Fractures in Men (MrOS) study - Lane, Nancy E; Parimi, Neeta; Corr, Maripat; Yao, Wei; Cauley, Jane A; Nielson, Carrie M; Ix, Joseph H; Kado, Deborah; Orwoll, Eric (Journal of bone and mineral research, 2013)
ABSTRACT Normal mineral metabolism is critical for skeletal integrity, and recently serum fibroblast growth factor 23 (FGF23) levels were found to be directly related to overall fracture risk in elderly Swedish men. To confirm this association, we performed a prospective case‐cohort study to understand the relation of FGF23 and fracture risk in older white men enrolled in the Osteoporotic Fractures in Men (MrOS) study. In the cohort of 5994 men attending the baseline MrOS examination, we evaluated a subgroup of 387 men with incident nonvertebral fracture including 73 hip fractures and a sample of 1385 men randomly selected from the cohort with baseline mineral and calcium hormone measurements. FGF23 was measured in baseline serum samples by ELISA (Millipore, Billerica, MA, USA). Modified Cox proportional hazards models that account for case‐cohort study design were used to estimate the relative hazards (RH) of fracture in men across quartiles of FGF23. Subjects were also stratified by renal function, and RH per strata was estimated in men with the highest quartile of FGF23 compared with quartiles 3, 2, and 1. Overall, there was no difference in risk of nonspine or hip fracture by baseline FGF23. However, associations differed by strata of eGFRCrCy. Among men with eGFRCrCys <60 mL/min/1.73 m2 (n = 73/313 nonspine fractures), the RH in the highest quartile of FGF23 compared with the rest was 2.02 (95% confidence interval [CI] 1.07–3.79), but in men with eGFRCrCy, >60 mL/min/1.73 m2 (304/1370 fractures) the RH was 0.91 (95% CI 0.66–1.25) after adjustment for age, clinic site, body mass index, race, total hip bone mineral density, vitamin D, parathyroid hormone, alcohol use, physical activity, fracture history, and serum phosphorus. Serum FGF23 levels are not associated with incident fractures in elderly men overall. However, higher levels of serum FGF23 are associated with fracture risk in those with poor renal function. © 2013 American Society for Bone and Mineral Research.